BEHAVIOR OF PERSONAL PROTECTIVE EQUIPMENT (PPE) USE IN THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY (OSH) - Darusman, Dadan Herman; Ruliana, Titin; Irwan, Sayid (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this research is to analyze the behavior of using Personal Protective Equipment (PPE) in the implementation of Occupational Health and Safety (OHS). The behavior of using Personal Protective Equipment consists of government regulations, company policies, and employee compliance. Design/methodology/approach: This research uses a descriptive quantitative approach. The data collection techniques include questionnaires and documentation. The data analysis tool used is regression and path analysis with SPSS application. Findings: The results of the study show that government regulations, company policies, and employee compliance do not have a significant effect on the behavior of using PPE by workers. Additionally, government regulations and employee compliance do not have a direct significant effect on OSH implementation. However, the behavior of using PPE and company policies have a direct significant effect on OSH implementation. Indirectly, government regulations have a significant effect on OSH implementation through the behavior of using PPE. This study contributes to enriching the understanding of the factors that influence the implementation of OSH in the forestry industry